THE DETERMINANT FACTORS OF PROFITABILITY ON SHARIA RURAL BANKS IN INDONESIA - Devita Rahma Aryati; Purwanto Purwanto (Management and Leadership Study Programme, 2019)
This research aimed to empirically examine the determinants of profitability of Sharia rural banks in Indonesia with quarterly period of time from 2014Q1 to 2018Q3. This research uses cross-sectional data of quarterly financial report and macroeconomic variables in Indonesia. The study is processed and analyzed quantitatively by using multiple regression. This research is using 8 Sharia rural banks in Indonesia with the total of 152 data used. The research reveals that inflation and NPF have no significant influence towards profitability of Sharia rural banks in Indonesia. While, the other four variables, GDP, CAR, FDR and OER are significantly influence the profitability of Sharia rural banks in Indonesia as much as 31.6%. In terms of variables, GDP, CAR and FDR are positively significant influence the profitability, while OER has negatively significant influence the profitability of Sharia rural banks in Indonesia.